Rapid identification of Lonicera japonica via Proofman-LMTIA technology - Xiaodong Zhang; Caixia Li; Dejia Lan; Jinxin Liu; Deguo Wang (Scientific Reports)
Abstract The study introduces a novel, rapid and precise method for identifying Lonicera japonica (JYH), an important medicinal herb, utilizing Proofman-LMTIA (Proofman probe-ladder melting temperature isothermal amplification) technology. Based on the 5.8 S-ITS2 rDNA sequence, specific primers and Proofman probes were designed to distinguish JYH from similar species, addressing the frequent market adulteration. The method’s optimal reaction conditions were established at 67 °C, ensuring high specificity. Sensitivity test demonstrated this method could detect as little as 10 pg/µL of JYH genomic DNA, with a detection limit of 1% (v/v) in adulteration experiments. The Proofman-LMTIA method successfully authenticated all eight market slice samples of JYH, six drugs and one solid beverage, achieving a 100% positive detection rate. This technique represents a significant advancement in medicinal material quality control, ensuring the JYH authenticity. These findings underscore the potential of the Proofman-LMTIA as a reliable, cost-effective, and user-friendly tool for real-time quality assessment in the herbal medicine industry.